2016
DOI: 10.1007/s00199-016-0986-z
|View full text |Cite
|
Sign up to set email alerts
|

Debt and welfare in economies with land

Abstract: In a stochastic economy of overlapping generations subject to uninsurable risks, debt can implement Pareto improvements in welfare. This is the case even in the presence of long-lived assets and no short sales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…While Kehoe and Pastorino argue that rich enough financial markets can obviate the need for intervention by an outside authority, Kokonas and Polemarchakis (2017) show that such interventions can be welfare improving in environments where market outcomes are not constrained optimal. Kokonas and Polemarchakis (2017) extend the analysis of Demange (2002), who had studied an economy of overlapping generations with life spans of two periods, one commodity at each date, and uninsurable idiosyncratic uncertainty on endowments. Demange demonstrated that a long-lived asset, land, traded subject to a ban on short sales ensured the constrained optimality of competitive allocations.…”
Section: Theories Of Debtmentioning
confidence: 94%
“…While Kehoe and Pastorino argue that rich enough financial markets can obviate the need for intervention by an outside authority, Kokonas and Polemarchakis (2017) show that such interventions can be welfare improving in environments where market outcomes are not constrained optimal. Kokonas and Polemarchakis (2017) extend the analysis of Demange (2002), who had studied an economy of overlapping generations with life spans of two periods, one commodity at each date, and uninsurable idiosyncratic uncertainty on endowments. Demange demonstrated that a long-lived asset, land, traded subject to a ban on short sales ensured the constrained optimality of competitive allocations.…”
Section: Theories Of Debtmentioning
confidence: 94%